Репродуктивная система клеща Varroa jacobsoni. II. Репродуктивная система самца и сперматогенез - Акимов, И.А.; Ястребцов, А.В. (Вестник зоологии, 1985)
Reproductive system of Varroa jacobsoni male is represented by horse shoe-shaped testicle, paired vas deferens, ejaculatory duct and unpaired accessory gland. Five structurally distinct cell types are recognized in the accesory gland. Germarium absence is shown in adult male testicles, so that reproductive capacity realization depends on qualities acquired during instar development. No meiosis takes place during spermatogenesis. During its life, a male produces ca. 600 spermatids (prespermatozoa). Spermatogenesis is completed at the stage of spermatids, spermiogenesis continues within female's sacculus foemineus. Adult male activity is restricted to reproduction, other important organic functions are respectively suppressed. Male's chelicerae are adjusted for copulation only and cannot bear any other functions. Reproductive system development during male nymphal stages is strongly connected with feeding on the bee brood.